Scientific-methodical support of gifted teenagers in creative education - Valentina G. Ryndak; Ekaterina S. Mikhaleva (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article actualizes the importance of the development of talented teenager potential for productive relationship with society through the acquisition of a teenager personality tumors ("Actual Self", "Potential Self", "Perspective Self"). It is noted that current gifted adolescents are not fully ready to develop their potential and most of them are aware of the significance of their potential and the implementation of their activities for society. The article examines the role and place of scientific and methodological support in the development of potential of gifted adolescents in creative education, the interaction of actors in the triad "co-creation - collaboration - self-education," forming a representation of the Other in the development of their potential and creating an atmosphere of creativity in creative-reflective environment. The material for this study consists of the test results, completing tasks, monitoring the activities of adolescents, content analysis. The study was confirmed using statistical significance of the G-criterion of signs (by D.B. Owen), correlation analysis and analysis of the author’s experience. The integrative characteristic of personality of a gifted teenager is given. The growth of teenagers’ responsibility in the field of studying and development of their own potential is marked.